2018
DOI: 10.1097/md.0000000000012278
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes of patients with non-bacteremic pneumonia caused by extensively drug-resistant Acinetobacter calcoaceticus-Acinetobacter baumannii complex isolates

Abstract: Few therapeutic options exist for various infections caused by extensively drug-resistant Acinetobacter calcoaceticus-Acinetobacter baumannii (XDR-Acb) complex isolates, including pneumonia. This study investigated the clinical efficacy between aerosolized colistimethate sodium (AS-CMS, 2 million units thrice a day) treatment alone or in combination with standard-dose tigecycline (TGC) in patients with non-bacteremic pneumonia due to XDR-Acb, and explored the factors influencing patients’ 30-day mortality.A 1:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…A Spanish study investigating the outcomes of ICU patients with VAP caused by P. aeruginosa observed that initial use of antibiotic combination therapy (mainly anti-pseudomonal β-lactam plus an aminoglycoside or an anti-pseudomonal fluoroquinolone agent) indeed significantly reduced the likelihood of inappropriate therapy, which was strongly associated with higher case-fatality risk [97]. Nevertheless, in distinction from two guidelines [11,14], there were many diversified regimens of antibiotic combinations proposed against clinical infections due to isolates of CR-Acinetobacter baumannii complex species [59,75,80,[98][99][100], as well as CRE [34,69,94,101]. Despite no reduction of mortality rates [11], a useful de-escalation of an antibiotic has the benefit of decreasing resistance burden.…”
Section: Discussionmentioning
confidence: 99%
“…A Spanish study investigating the outcomes of ICU patients with VAP caused by P. aeruginosa observed that initial use of antibiotic combination therapy (mainly anti-pseudomonal β-lactam plus an aminoglycoside or an anti-pseudomonal fluoroquinolone agent) indeed significantly reduced the likelihood of inappropriate therapy, which was strongly associated with higher case-fatality risk [97]. Nevertheless, in distinction from two guidelines [11,14], there were many diversified regimens of antibiotic combinations proposed against clinical infections due to isolates of CR-Acinetobacter baumannii complex species [59,75,80,[98][99][100], as well as CRE [34,69,94,101]. Despite no reduction of mortality rates [11], a useful de-escalation of an antibiotic has the benefit of decreasing resistance burden.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of XDRAB has been associated with high in-hospital and 30-day mortality in prior studies. [8][9][10] Although some of this association is explained by the propensity of Acinetobacter to infect hospitalized, medically complex patients with high baseline risk for mortality, prior studies have shown substantial attributable mortality from MDRAB infections specifically. 4,12 Our study had several important limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Existing data on XDRAB come largely from smaller, single-center studies conducted outside the United States. [8][9][10] In this national cohort study, we used data from US Department of Veterans' Affairs (VA) hospitals to describe the epidemiology, clinical characteristics, and outcomes for patients with XDRAB in the VA.…”
mentioning
confidence: 99%
“…As a result of the impact of assessment criteria and administration route on observed nephrotoxicity rates, subsequent subgroup analyses of the nephrotoxicity rate were performed in a secondary analysis population that included only studies using internationally recognized assessment criteria (RIFLE, AKIN or KDIGO) and excluded ten studies in which less than 50% patients received systemic polymyxins [19,26,53,66,71,119,143,147,155,243]. The results of these subanalyses are presented here, whereas metaanalyses of the nephrotoxicity rate including all 237 studies regardless of AKI criteria and administration route are presented in Supplementary Figs S1 to S17.…”
Section: Nephrotoxicitymentioning
confidence: 99%